Utilization patterns and potential cost savings of generic cardiovascular medications at private community pharmacies in the Johannesburg area: an analysis of medical claims retrospectively. - Govender, Sagel (My University, 2014)
Cardiovascular disease is a leading cause of death worldwide (Kishore et al., 2011), therefore how to prevent and treat this condition is of great importance to health care professionals and patients. Patients struggle to afford these medications which can ultimately influence their health outcome. Treatment of cardiovascular disease conditions may require several drugs and this causes an increase in health cost to the patient (Burapadaja Siriporn et al., 2007).The promotion of the use of generic medication and generic substitution is seen as one of the approaches to improve access to cardiovascular medications (Kishore et al., 2011; Kesselheim et al., 2008). Generic medications play an important role in reducing health care costs and in increasing access to healthcare. A large number of branded or innovator drugs and molecules are no longer protected by their patents or will be reaching patent expiration soon. Therefore there is an increased interest in research on generic drug competition and its effect on the market. Once generics enter the market, they have many effects on areas such as market share, prices and quantities sold (Gonzalez et al., 2008). The objective of this study was to determine the usage patterns of generic cardiovascular medications and possible cost savings that can be achieved by maximum generic substitution in the private community pharmacy health care environment in the Johannesburg area. Ten oral solid drug pairs experiencing generic substitution were investigated at four private community pharmacies that provided pharmaceutical products and services. The study was a quantitative, retrospective study of medical claims. Data on computerized drug claims were provided by a South African pharmaceutical service provider. Data was extracted and analysed of patients who receive one or more cardiovascular drugs for the period of June 2009 to May 2011. The results of this study showed that the cardiovascular (CVS) medications under study accounted for 21 817 of the total number of 282 109 items dispensed at all pharmacies for the study period which equals to 7.7%. Of the total of 21 817, the innovator CVS drugs accounted for a volume of 6 527 (29.9%) and the generics 15 290 (70.1%) of all the study CVS items dispensed. There was a decline in terms of percentage of innovator products (9.7%) and a corresponding increase in generic products by the same percentage from beginning to end of the study period in terms of items dispensed. The total cost of the study CVS innovator and generic drugs was R3 249k. This accounted for 7.4% of the total cost of all items dispensed for all the study pharmacies which was R43 672k. Of the total of R3 249k, a cost of R1 240k (38.2%) accounted for the innovator items and R2 009k (61.8%) accounted for the generic items. The average cost per CVS item for the entire study period was R149. The innovator average cost per item dispensed was R190 (±R93.28) and for generic R131 (±R59.55). There was a 9.9% decrease in percentage of innovator total cost and a corresponding 9.9% increase in percentage of generic cost from the beginning until end of the study period. The following was also revealed: the average cost per item decreased by R18 (from R156 during P1 to R138 for P6). The average cost per innovator item dispensed decreased by R10 (from R191 during P1 to R181 for P6) and the average cost per generic item decreased by R14 (from R138 during P1 to R124 for P6). The cost prevalence index (CPI) for innovator items was fairly expensive compared to generic medicine because the value of CPI was larger than 1. Potential cost savings of R576k would have been achieved if the least expensive generic was substituted during each period for the entire study period. If the most expensive generic was substituted, the potential cost savings would have been R448k. (Note: k =1000). Recommendations in this field of study for future research were also done.
Keywords: Drug Costs; Drugs, Generic; Costs and Cost Analysis